Application of Sustainable Drainage System as a Model of Flood Control with Environmental Insight in Medan City - Harisdani, Devin Defriza; Hadinugroho, Dwi Lindarto; Sembiring, Dicky Andrea; Sembiring, Robi Arianta (Talenta Publisher, 2022)
The area around the Universitas Sumatera Utara Campus, Medan city, is an area that is often hit by floods, especially when there is quite heavy rain with a fairly long duration. Based on initial observations, it can be said that this is due to the drainage channel being unable to accommodate the high rainwater discharge. To overcome this, the 2021 USU TALENTA Community Service Program offered a solution by creating a sustainable drainage system that is environmentally insight. The solution starts with the smallest thing that each household in the affected area can do, namely through making biopori holes. In addition to biopori, another solution taken is through the construction of infiltration wells and groundwater tanks. Conducted training and simulation activities on these three solutions of environmentally sustainable drainage systems. It is hoped that it will gradually reduce water runoff directly into the city drainage, but the water can be partially absorbed into the ground first, to reduce standing water which can eventually cause flooding.